2019
DOI: 10.1088/1748-9326/ab239c
|View full text |Cite
|
Sign up to set email alerts
|

Global soil acidification impacts on belowground processes

Abstract: With continuous nitrogen (N) enrichment and sulfur (S) deposition, soil acidification has accelerated and become a global environmental issue. However, a full understanding of the general pattern of ecosystem belowground processes in response to soil acidification due to the impacting factors remains elusive. We conducted a meta-analysis of soil acidification impacts on belowground functions using 304 observations from 49 independent studies, mainly including soil cations, soil nutrient, respiration, root and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 60 publications
6
83
1
1
Order By: Relevance
“…Similarly, previous studies have reported that productivity declines were observed in long-term monoculture Chinese r plantations [15,18]. The CP soil suppressed growth and leaf photosynthesis, as shown in other studies [19], which might be due to three reasons: depletion of nutrient elements, soil acidi cation and imbalance of soil microbes [14,20,21]. Generally, soil degradation in the continuous cropping system of our study appeared to be less serious than expected based on previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, previous studies have reported that productivity declines were observed in long-term monoculture Chinese r plantations [15,18]. The CP soil suppressed growth and leaf photosynthesis, as shown in other studies [19], which might be due to three reasons: depletion of nutrient elements, soil acidi cation and imbalance of soil microbes [14,20,21]. Generally, soil degradation in the continuous cropping system of our study appeared to be less serious than expected based on previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…Root biomass and R:S generally increases with soil alkalinity (Figure 3,Supplementary Figures 11,12,13). Low pH is toxic to biological activities and roots, especially as fine roots are sensitive to soil acidification, as revealed by a recent meta-analysis (Cheng Meng et al, 2019). Our results also indicate overall positive correlations between CEC, BS and R:S, but the processes that may account for these correlations are less clear from literature.…”
supporting
confidence: 64%
“…Dai et al (2017) point out that approximately 50% of the world's arable soils are acidic, with areas further increasing in recent years. It is well known that acid soils can alter soil carbon (C) and nutrient cycling and adversely influence the growth of plant and soil biota, and threaten terrestrial ecosystem functions (e.g., net primary production and species richness; Meng et al, 2019;Stevens et al, 2010;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%